Hard News dalam Instagram: Strategi dan Efektivitas Komunikasi Krisis Pemerintah melalui Akun @Indonesiago.id pada Banjir Sumatra 2025: Periode 1 - 31 Desember 2025 - Nissaq, Mona Azhari; Samudera, Mochamad Yoga (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study examines the strategy and effectiveness of government crisis communication through Instagram, particularly in packaging hard news content on the @indonesiago.id account during the Sumatra flood disaster from December 1 to 31, 2025. The research employs a qualitative descriptive content analysis of 292 relevant posts. The findings reveal that the government adopts an adaptive hard news strategy, maintaining factual accuracy while adjusting content formats to align with the visual, emotional, and interactive nature of social media platforms. Short-form video content (Reels) is identified as the most effective format in generating impressions and reach, especially when combining emotional storytelling with concrete data. Furthermore, communication effectiveness is multidimensional, reflected through a combination of impressions, reach, and engagement metrics. The study also highlights the significant role of platform affordances in shaping government crisis communication strategies in the digital era. Theoretically, this research contributes to the development of hard news concepts in social media contexts and the expansion of crisis communication models, while practically offering recommendations for improving public communication during crises.